Influence of pulse laser energy on the Nickel plasma characteristics that produced in laser-induced plasma system (Baghdad Science Journal, 2024)
Optical Emission Spectrometry technique (OES) is used to analyze the plasma generated from a (Ni) target illuminated with a Q- Switched (Nd:YAG) laser at various energies in the air.  Boltzmann-Plot and Stark broadening methods were used to calculate the plasma parameters including electron density (ne), electron temperature (Te), plasma frequency (fp), and Debye length (λD). It is shown that the values of (ne), (Te), (λD) and (fp) increase with increasing laser energy with the calculated electron temperature values ranging between 0.934 - 1.479 eV.